Analysis of maternal and fetal outcome in gestational diabetes mellitus - Sharma, Shuchi; Das, Jayita; Sharma, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Diabetes is the most common medical complication of pregnancy. Glycemic control throughout pregnancy and a late-pregnancy HbA1c level <6.5 percent leads to reduced rates of adverse obstetrical and neonatal outcomes. Methods: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology, Shri Lal Bahadur Shastri medical college Mandi, Himachal Pradesh for a period of one and half years from 1st January 2023 to 30th June 2024. All the pregnant women with gestational diabetes mellitus were included in the study. Results: The prevalence of gestational diabetes mellitus was 128 (2.02%). The most common age group was 26-30 years. There were 7.8% obese and 90.6% over weight patients. Most of the patients (54.68%) were treated by medical nutrition therapy (MNT) followed by insulin (34.3%). The most common maternal complication was hypertension (15.6%) and 31.25% babies had admission in neonatal care unit. 10 (7.8%) babies had birth asphyxia and neonatal death. Conclusions: Single step screening with 75 gm OGTT is being followed in our state and the universal screening has improved the maternal and neonatal outcomes with GDM. Enhanced screening, timely intervention and motivation of the GDM patients on diet control, metformin or insulin to achieve euglycaemia can reduce maternal, fetal and neonatal complications.